Fatal delayed rupture of the subclavian artery in a patient with first‐rib fracture caused by blunt trauma. Issue 3 (30th January 2017) - Yonezawa, Naoki; Nakayama, Yusuke; Takei, Tetsuhiro; Toh, Masafumi; Asano, Mitsutoshi; Imamura, Tomonori; Ito, Toshitaka
Key Clinical Message: This case highlights the probable association of significantly displaced posterior first‐rib fracture and jagged edges of the fracture line following blunt chest trauma with delayed ipsilateral subclavian artery rupture. Early angiography and first‐rib repair should promptly be considered under such circumstances. Abstract : This case highlights the probable association of significantly displaced posterior first‐rib fracture and jagged edges of the fracture line following blunt chest trauma with delayed ipsilateral subclavian artery rupture. Early angiography and first‐rib repair should promptly be considered under such circumstances.